The radical scavenging activity of 2-2’ diphenyl -1- picrylhydrazil (DPPH) on the methanol extracts and Ethyl acetate fractions of red dragon fruit peel (Hylocereus polyrhizus (F.A.C.Weber) Britton dan Rose) - Sri Wahdaningsih; Sugeng Riyanto; Retno Murwanti (International Journal of Phytomedicine, 2017)
Red dragon fruit (H. Polyrhizus) is one of the the plants that has a great potential as natural antioxidant. This study tested the activity of radical scavenging of 2-2’ diphenyl -1- pikril hidrazil (DPPH) in the methanol extract, as well as in the soluble and insoluble fractions of ethyl acetate of red dragon fruit peel. This research is carried out through various stages, such as: extraction and fractionation to obtain both insoluble fraction and soluble fractions of ethyl acetate. Antioxidant activity test is conducted by the method of thin layer chromatography and spectrophotometry. Antioxidant activity test, IC50 values of methanol extract, ethyl acetate soluble fraction, and insoluble fraction of ethyl acetate had been obtained consecutively as much as 241.19 µg /mL, 8.34 µg/mL, 46.84 µg/mL. The soluble fraction of ethyl acetate had greater antioxidant activity compared to the methanol extract and the insoluble fractions of ethyl acetate.